The missing piece [compact disc, unabridged] - Lescroart, John T. (Lescroart, John T. Dismas Hardy novel., 2022)
"Having joined the "dark side" after years spent prosecuting criminals as the San Francisco DA, defense attorney Wes Farrell is experiencing a crisis of faith. How can he in good conscience defend clients whom, in his estimation, are most likely guilty? In his role as DA, Farrell had helped put away Paul Riley, a young man charged for the rape and murder of his then-girlfriend Dana Rush, only for Riley to later be released from his life sentence - after eleven years of time served - when the Exoneration Initiative unearthed DNA evidence that pinned the crime on someone else. But just months after walking free, Riley is murdered at his home, and Farrell is roped back into defending the prime suspect: Dana's father, Doug Rush. An eyewitness - Paul's father - claims he saw Doug fleeing the scene of the crime. Presuming Doug's guilt despite his insistence that he didn't do it, yet prepared to cut the best possible deal for the man whom the system failed, Wes is left in the dust when his client suddenly vanishes before his bail hearing. Worried that he failed his client, Farrell turns to his colleague, seasoned attorney Dismas Hardy, and their buddy, retired police lieutenant-turned PI Abe Glitsky, to help track down their missing defendant... but will they find him alive? Full of twists, turns and masterful misdirection, John Lescroart's latest is a nail-biter that once again exposes the blind spots and biases of our justice system while shining a light on the decent people out there who fight to restore the balance"--